A Novel Method to Identify Three Quality Grades of Herbal Medicine Ophiopogonis Radix by Microscopic Quantification - Yu, Kunzi; Liu, Wei; Zhang, Nanping; Cheng, Xianlong; Zhou, Shiyu; Zuo, Tiantian; Kang, Shuai; Wei, Feng; Ma, Shuangcheng (Frontiers in Pharmacology, 2021)
Maidong, the root tuber of Ophiopogon japonicus (Thunb.) Ker Gawl., is a commonly used herbal medicine in China. There are three quality grades of Maidong according to traditional opinion and modern researches: superior quality (Zhe-maidong), medium quality (Chuan-maidong), and poorest quality (Chuan-maidong with paclobutrazol, which is a kind of plant growth regulator). However, no efficient way to distinguish the three quality grades of Maidong exists, thus, the herbal markets and botanical pharmacies are flooded with Chuan-maidong with paclobutrazol. To ensure the safety and quality of Maidong, a comparative microscopic study was performed on three quality grades of Maidong. The result was used to establish a microscopic quantification method based on the area ratio between xylem and pith to distinguish the three quality grades of Maidong. Subsequently, Maidong from of regional markets was evaluated by this method. In this study, we developed a novel quantification method to identify the three quality grades of Maidong, which could in turn make efforts on the quality improvement of Maidong. Our study is the first to demonstrate that microscopic technology could be used to distinguish different quality grades of a specific herbal medicine.